Analisis Faktor Faktor Yang Mempengaruhi Pengalokasian Anggaran Belanja Modal - Suhesti Ningsih; Intan Indah Permatasari; Rukmini Rukmini (ITB AAS INDONESIA, 2024)
This research is a type of quantitative research aiming at determine the effect of economic growth, local revenue and general allocation funds on capital expenditure of all sub-districts of Karanganyar district from 2018 to 2022. The data used in this research are secondary data obtained from budget realization report and economic growth. Population in this research 17 sub-districts in Karanganyar regency. The sampling technique in this research used a saturated sampling technique. The sample in this research wa 17 sub-districts within 5 years so the sample is 85. The data analysis methods used are classical acceptance and multiple linear regression tests, F-tests, t-test and R2-tests. The results of the F-tests on the variables of economic growth, native local income, and general allocation funds influence government policies in allocating capital expenditures. The t-test results show that the variables economic growth and village income have a large effect on investment, while the general allocation fund has no effect on investment Keywords: Economic growth, capital investment, general grants, local revenues